2004
DOI: 10.1099/vir.0.19583-0
|View full text |Cite
|
Sign up to set email alerts
|

The C-terminal 33 amino acids of the cucumber mosaic virus 3a protein affect virus movement, RNA binding and inhibition of infection and translation

Abstract: The capsid protein (CP) of Cucumber mosaic virus (CMV) is required for cell-to-cell movement, mediated by the 3a movement protein (MP). Deletion of the C-terminal 33 amino acids of the CMV 3a MP (in the mutant designated 3aDC33 MP) resulted in CP-independent cell-to-cell movement, but not long-distance movement. RNA-binding studies done in vitro using isolated bacterially expressed MP showed that the 3aDC33 MP bound RNA more strongly, with fewer regions sensitive to RNase and formed cooperatively bound complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 34 publications
0
32
0
1
Order By: Relevance
“…This suggestion is supported by our covariation analyses, which reveal that the C-terminal amino acids of MP are coevolving with the N-terminal region of CP (CP CG1). This suggestion gets further support from evidence for such contact in other members of the Bromoviridae family such as CMV (26), BMV (47), and AMV (41,43).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…This suggestion is supported by our covariation analyses, which reveal that the C-terminal amino acids of MP are coevolving with the N-terminal region of CP (CP CG1). This suggestion gets further support from evidence for such contact in other members of the Bromoviridae family such as CMV (26), BMV (47), and AMV (41,43).…”
Section: Discussionmentioning
confidence: 74%
“…Furthermore, recently Sánchez-Navarro et al (43) have shown that the 44 amino acids at the AMV MP C terminus physically interact with CP to elicit movement. Apparently, the C terminus of AMV MP confers specificity on the transport process (41) as it does in the cases of BMV (47) and CMV (26). MPs of PNRSV, AMV, CMV, and BMV have been shown to have an RNA-binding domain located at the N terminus of the protein in the first two cases or at the C terminus in the last two (3,4,7,21).…”
mentioning
confidence: 99%
“…The failure to accumulate in upper leaves is probably due to an inability of D RNA 3-1 to move systemically in the absence of encapsidation rather than an inhibition of cellto-cell movement, since the latter process does not require either encapsidation or interaction between CMV RNAs and the capsid protein (Kim et al, 2004). It seems likely that virion formation is essential for systemic movement in squash, since it was shown that CMV capsid protein mutants that did not form virions still supported systemic movement in some Nicotiana species but not in squash .…”
Section: Discussionmentioning
confidence: 99%
“…replication and/or translation; Bol, 2005). In the case of the CMV MP, the deletion of the dispensable C terminus region induced an increase of the MP RNA-binding affinity, indicating that perhaps both effects, the lack of the C terminus and the increasing of the RNA affinity, could be required to convert a CP-dependent protein into a CP-independent one (Kim et al, 2004). In BMV, MP-CP interaction requires mature virion formation although an isolate has been described, capable to infect dicot plants, that is able to move between cells independently of CP (Takeda et al, 2004(Takeda et al, , 2005.…”
Section: Analysis Of the C-terminal Region Of Pnrsv Mpmentioning
confidence: 99%